Green synthesis of Ca(OH)2 nanoparticles from chicken eggshell waste as antibacterial agent - Purnomo, Agus; Djayasinga, Rodhiansyah (International Journal of Public Health Science (IJPHS), 2025)
Chicken eggshell waste, though abundant in CaCO3 that can be converted into various products like calcium hydroxide nanoparticles (NPs), has received limited attention. This study aimed to synthesize calcium hydroxide NPs from eggshell waste and evaluate their antibacterial properties against Staphylococcus aureus and Escherichia coli. The researchers employed a top-down approach with thermal decomposition to produce environmental-friendly calcium hydroxide NPs, and conducted in vitro tests to assess their antibacterial activity, with and without exposure to sunlight. The minimum inhibitory concentration and disc diffusion methods were used to evaluate the antibacterial effects. X-Ray diffraction analysis confirmed the synthesis of calcium hydroxide NPs. Further, a paired T-test showed that the calcium hydroxide NPs exhibited significant antibacterial activity against both bacterial through photocatalytic mechanisms, in comparison to their performance without such techniques. The utilization of green synthesis techniques to produce materials with potential antimicrobial applications presents significant developmental opportunities for the future.